Examining the Impact of PP 23/2018 policy through the Tax Compliance Factor of Tanah Abang Traders - Wardinto P; Gunadi . (Program Pascasarjana Universitas Negeri Makassar, 2021)
This study aims to examine the factors that can affect tax compliance at Tanah Abang Market traders, which are the tax rate, perceived opportunity to evade, legal certainty, and group influence. This study uses a quantitative method with a positivism approach which examines social phenomena and captures the perceptions of MSEs actors on the determinants of tax compliance. The sample in this study were 154 MSEs respondents in Tanah Abang Market that were scope into Central Jakarta Regional Tax Office, both private individuals and corporate taxpayers. The results of the study revealed that the tax rate, perceived opportunity to evade, legal certainty, and group influence have a positive effect on tax compliance at Tanah Abang Market traders, but not significant only in the tax rate variable. This is very useful for the DGT authority and the Fiscal Policy Agency as policymakers that the reduction in tax rates does not affect the compliance behavior of MSEs traders and increase monitoring of compliance with MSEs taxpayers through derivative regulations on the implementation of supervision of MSEs taxpayers.